Features of service delivery agencies of government revenue in the Republic of Kazakhstan - Yessengeldina, A.S.; Seitalinova, A.S.; Kosdauletova, R.Ye. (BUKETOV BUSINESS REVIEW, 2017)
The article considers the content and significance of the concept of rendering public services. The state services rendered are grouped according to various criteria: voluntary and compulsory, simple and complex. Authors consider subjects of state authority as subjects, and as objects of application of individuals and legal entities submitted for receiving state services. The article focuses on the specifics of state services provided by the State Revenue Committee of the Ministry of Finance of the Republic of Kazakhstan. State services provided by the State Revenue Committee of the Ministry of Finance of the Republic of Kazakhstan are classified according to the following characteristics: by service recipients, by types, by terms of provision, by forms of services. The authors, having analyzed the activities of the State Revenue Committee of the Ministry of Finance of the Republic of Kazakhstan in providing public services, offered the following ways of improvement: using information and communication technologies to increase the number of electronic forms of public services; Introduce a «payment gateway» for the implementation of tax and other mandatory payments; To systematize and integrate information resources of the State Revenue Committee with other state bodies; For the rapid processing of information in the public revenue sectors, use the «cloud storage» (G-Cloud); To develop a mobile application for tax reporting.